Conceptualizing stress associated with clinical experiences of Korean counseling repatriates - Kim, Eunha; Bae, Suyeon; Kim, Jiwon (Journal of Multicultural Counseling and Development, 2024)
This study explored stress associated with clinical experiences of Korean counseling repatriates who returned to South Korea after obtaining their doctoral degree in the United States. Concept mapping revealed six major clusters of stressors: difficulties associated with language and communication, cultural differences between therapists and clients, clients’ attitudes toward and expectations regarding therapy, lack of ethical standards and licensure issues, hierarchical collectivistic working culture, and mental health system not being well-established.
Keywords: asesoramiento; counseling; reentrada/reentrado; reentry; repatriar; repatriates